Studi Pemanfaatan Biogas dari Limbah Rumah Potong Hewan untuk Mendukung Ketahanan Energi di Kota Bandung - Anita Juraida; Yudha Prambudia; Ari Rahman (Jurnal Wilayah dan Lingkungan, 2019)
Energy demand, particularly electricity for many activities, increases in line with the growth of urban population. Nowadays, most of energy supply in urban area is still dominated by the fossil fuel sources. As the use of fossil fuel increases, so does the greenhouse gas emission closely linked to global warming effects. Moreover, population growth also implies on waste production resulted from industrial and domestic activities. This paper applies waste to energy concept by estimating potential renewable energy from the slaughterhouse waste in Bandung City, Indonesia. This study is aimed to predict the potential contribution of waste from cattle, consisting of blood, rumen and feces from the slaughterhouses for biogas production. This research applies direct observation technique, interview and literature review methods. The location of this research was at the public and private slaughterhouses in Ciroyom, Cirangrang, and Regol of the Bandung City. The results showed that biogas could be produced by 139,977 m3/year equivalent to 658 MWh/year of electricity production. To support the city’s energy security, this potential energy source may contribute around 49.8% of the household electricity supply equivalent to 16.7% of the total electricity supply in Bandung City. This finding could be beneficial to the larger pilot study concerning the sustainable city program.